Strain Localization and Seismic Properties in the Heterogeneous Ailaoshan‐Red River Shear Zone, Southeast Asia - Junyu Li; Shuyun Cao (Geochemistry, Geophysics, Geosystems)
Abstract Strain localization is crucial in developing crustal‐scale shear zones; however, a systematic analysis of deformation characteristics and their impact on seismic properties is still lacking. This study provides a comprehensive analysis of migmatites and granitic mylonites in the Ailaoshan‐Red River shear zone (ASRR‐SZ), incorporating detailed field observations, microstructure analysis, mineral crystallographic preferred orientations, rheological parameters, and seismic properties. Pre‐existing compositional and mechanical anisotropies significantly influence strain localization in the ASRR‐SZ. The southern part of the ASRR‐SZ is primarily characterized by crustal anatexis, suggesting these regions as potential initiation sites for strain localization. Strain characteristics in the ASRR‐SZ manifest in deformation temperatures (three ranges, ∼400–440°C, ∼470–500°C, and ∼730°C), differential stress (concentrated at 15.9–65.1 MPa), and strain rate (concentrated at 10−13–10−11 s−1). Notably, strain localization significantly alters the rock fabric and further affects the seismic properties of rocks. Significant differences in Vp values and orientations are noted between melanosomes (anisotropy of P‐waves: AVp = 6.8%–17.9%, Max. Vp along the X‐axis) and leucosomes (AVp = 3.4%–3.7%, Max. Vp along the Y‐axis). The seismic velocities and AVp in granitic mylonites exhibit a linear correlation with quartz content, and deformation conditions strongly influence their orientation. For a middle to lower crust thickness of ∼25 km, the delay times between fast and slow polarized shear waves are 0.3–0.66 s for granitic mylonites, 0.37–0.7 s for melanosomes, 0.22–0.31 s for leucosomes, 0.27–0.58 s for amphibolites, and 0.57–2.7 s for schists. The average delay time (dt) of these rocks along the ASRR‐SZ accounts for the observed delay time (dt = 0.58 s).